(NsTIHOTWORENIQ I PO\MY (B/ s (N~ASTX (B1s - (NgAMZATOW(B, (NrASULs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1980)
(Nw PERWYJ TOM sOBRANIQ SO^INENIJ NARODNOGO PO\TA dAGESTANA(B, (NrASULA gAMZATOWA(B, (NWKL@^ENY STIHOTWORENIQ IZ EGO KNIG (B"(NzEMLQ MOQ(B" (1948), "(NpESNI GOR(B" (1949), "(NgOD MOEGO ROVDENIQ(B" (1952), "(NsTIHOTWORENIQ(B" (1956), "(NdETI DOMA ODNOGO(B" (1956), "(NnOWAQ WSTRE^A(B" (1957), "(Nw GORAH MOE SERDCE(B" (1959) (NI DRUGIE(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\MYs